Disparities in trajectories of changes in the unhealthy food environment in New York City: A latent class growth analysis, 1990–2010. (August 2019) - Berger, Nicolas; Kaufman, Tanya K.; Bader, Michael D.M.; Rundle, Andrew G.; Mooney, Stephen J.; Neckerman, Kathryn M.; Lovasi, Gina S.
Abstract: Disparities in availability of food retailers in the residential environment may help explain racial/ethnic and socio-economic differences in obesity risk. Research is needed that describes whether food environment dynamics may contribute to equalizing conditions across neighborhoods or to amplifying existing inequalities over time. This study improves the understanding of how the BMI-unhealthy food environment has evolved over time in New York City. We use longitudinal census tract-level data from the National Establishment Time-Series (NETS) for New York City in the period 1990–2010 and implement latent class growth analysis (LCGA) to (1) examine trajectories of change in the number of unhealthy food outlets (characterized as selling calorie-dense foods such as pizza and pastries) at the census tract-level, and (2) examine how trajectories are related to socio-demographic characteristics of the census tract. Overall, the number of BMI-unhealthy food outlets increased between 1990 and 2010. We summarized trajectories of evolutions with a 5-class model that indicates a pattern of fanning out, such that census tracts with a higher initial number of BMI-unhealthy food outlets in 1990 experienced a more rapid increase over time. Finally, fully adjusted logistic regression models reveal a greater increase in BMI-unhealthy food outlets in census tracts with: higher baseline population size, lower baseline income, and lower proportion of Black residents. Greater BMI-unhealthy food outlet increases were also noted in the context of census tracts change suggestive of urbanization (increasing population density) or increasing purchasing power (increasing income). Highlights: Exposure to the unhealthy food environment increased between 1990 and 2010. We observed divergent trajectories of changes in the unhealthy food environment. Greater increases in exposure occurred in poorer and non-Black neighborhoods. Greater exposure was related to urbanization and increasing purchasing power.